2014
DOI: 10.1063/1.4864635
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive micromachined ultrasonic transducer arrays as tunable acoustic metamaterials

Abstract: Capacitive Micromachined Ultrasonic Transducers (CMUTs) operating in immersion support dispersive evanescent waves due to the subwavelength periodic structure of electrostatically actuated membranes in the array. Evanescent wave characteristics also depend on the membrane resonance which is modified by the externally applied bias voltage, offering a mechanism to tune the CMUT array as an acoustic metamaterial. The dispersion and tunability characteristics are examined using a computationally efficient, mutual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Overall, one observes a spurious resonance free range of frequencies between the first mode of the single CMUT membrane on the lower end and either Bragg or a higher order membrane mode resonance on the higher end [37,50]. The effect of Bragg's resonance and crosstalk is also observed in pressure sensitivity.…”
Section: A Receiver Analysismentioning
confidence: 86%
“…Overall, one observes a spurious resonance free range of frequencies between the first mode of the single CMUT membrane on the lower end and either Bragg or a higher order membrane mode resonance on the higher end [37,50]. The effect of Bragg's resonance and crosstalk is also observed in pressure sensitivity.…”
Section: A Receiver Analysismentioning
confidence: 86%
“…In the field of medical imaging, we, the authors of this study, developed new products, 22‐25 and other companies have also been developing products using CMUTs 26 . Furthermore, recently, there have been studies on acoustic filters whereby the properties of a CMUT‐structure acoustic metamaterial can be made variable by controlling the applied bias voltage 27 …”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, recently, there have been studies on acoustic filters whereby the properties of a CMUT-structure acoustic metamaterial can be made variable by controlling the applied bias voltage. 27 In this study, we focus on MUTs, which are being increasingly put into practical use, and propose a novel acoustic metamaterial-based acoustic impedance matching system that utilizes the structure of MUTs. In Section 2, we present the principle and structure for realizing MUT-type acoustic metamaterial-based acoustic matching, and an evaluation system based on numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to tune the response of such materials also remains limited, which is a roadblock for interacting with different devices and phenomena, for device multifunctionality, and for spatially tailoring the materials' effective properties for strategies such as transformation acoustics or topological design . Prior lattices and acoustic metamaterials operating in the MHz–GHz regime have experimentally demonstrated tuning of <20% to ≈90% of the bandgap center and stop band cutoff frequencies, respectively, and prior self‐assembled phononic crystals have demonstrated postassembly tuning of <20% of the bandgap center frequency. No prior studies have demonstrated the ability to tune a self‐assembled ultrasonic metamaterial in a spatially localized manner after fabrication of the crystal, which is particularly critical due to the sensitivity of most self‐assembly processes to the properties of the particles and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The tunability, which we note is nonreversible (in contrast to refs. ), is achieved through the use of optical‐microlensing to tailor nanocontact features. Our self‐assembled metamaterials mitigate the aforementioned manufacturing scalability challenges, and have been previously demonstrated in the context of, for instance, surface acoustic wave (SAW) filters to have massive attenuations of −0.25 dB µm −1 (similar to recent phononic crystal filters with −0.31 dB µm −1 attenuation).…”
Section: Introductionmentioning
confidence: 99%